Expansion of polyglutamine repeat in huntingtin leads to abnormal protein interactions involving calmodulin. - Bao, J (1996)
Huntington's disease (HD) is an inherited neurodegenerative disorder associated with expansion of a CAG repeat in the IT15 gene. The IT15 gene is translated to a protein product termed huntingtin that contains a polyglutamine (polyGln) tract. Recent investigations indicate that the cause of HD is expansion of the polyGln tract. However, the function of huntingtin and how the expanded polyGln tract causes HD is not known. We investigate potential protein-protein interactions of huntingtin using affinity resins. Huntingtin from brain extracts is retained on calmodulin(CAM)-Sepharose in a calcium-dependent fashion. We purify rat huntingtin to apparent homogeneity using a combination of DEAE-cellulose column chromatography, ammonium sulfate precipitation, and preparative SDS/PAGE. Purified rat huntingtin does not interact with CAM directly as revealed by 125I-CAM overlay. Huntingtin forms a large CAM-containing complex of over 1,000 kDa in the presence of calcium, which partially disassociates in the absence of calcium. Furthermore, an increased amount of mutant huntingtin from HD patient brains is retained on CAM-Sepharose compared to normal huntingtin from control patient brains, and the mutant allele is preferentially retained on CAM-Sepharose in the absence of calcium. These results suggest that huntingtin interacts with other proteins including CAM and that the expansion of polyGln alters this interaction.